Diagnóstico do perfil dos estabelecimentos do setor supermercadista de acordo com a legislação de alimentos - Brasil, Carla Cristina Bauermann (2011)
The competition and the concentration of business, observed in the Brazilian market, increase more and more the necessity of searching for quality and differentiation by the supermarket sector, seeing that the consumer is more and more demanding. Despite this, this segment remains little studied as for the hygienic-sanitary, food manipulators and managing conditions. Thus, this study aimed to develop and apply a specific list of Good Practices inspection for the supermarket sector; to characterize and verify the level of adequacy of this segment to the Good Practices; to identify the social- economical and demographic profile of managers and food manipulators in the establishments; and, to verify their level of knowledge in relation to the food security. The evaluation of hygienic-sanitary conditions was done in 69 establishments from the supermarket sectors which were registered at the National Health Surveillance Agency - VISA, during the period between April and July 2011 through the development and application of the list of Good Practices, having the current legislation as basis. He data were collected by in loco observation, using the List of Good Practices inspection, which were filled in by a technical and capable professional in the area of food quality. The data referring to the 345 food manipulators and 69 managers were obtained through interviews with questionnaires previously tested and approved by the Committee of Ethics in Research (CEP) from the Federal University of Santa Maria (UFSM). The data analysis revealed that the average percentage of general adequacy of the 69 establishments is of 29,07%, being that the blocks that show bigger conformity were related to the external area (64,73%) and storing at ambient temperature (64,13%), respectively. the establishments showed a less satisfying performance in the other blocks and sectors, mainly in the bakery and patisserie (14,93%), water supply (18,30%), food manipulators (21,01%), sausage and cold meats factory (36,38%), butcher and fishery (40,06%), beyond the items referring to the Good Practices documentation (4,97%), seeing that any establishment from the supermarket sector had the Good Practice Manual, the Operational Standard Procedures and the other necessary documents for the implementation of the quality systems. Beyond that, all establishments from the supermarket sector showed inefficiency to the application of the Good Practices. The information from the interviews done with the food manipulators and the establishment managers revealed that these professionals have right perceptions about the food hygiene and manipulation; however, the knowledge related to the food security may not result in its effective application. It is suggested greater applicability of the Good Practices in the establishments analyzed, as well as the adoption of programs for continuing capability for the food manipulators and establishment managers in order to guarantee the quality in the food production and manipulation. the results of this work evidence lacks in the procedures adopted in the segment in study, what allows to assume potentials and expressive risks of impulsive occurrence of diseases passed through food in these environments and the like, yet, the establishments where the research happened mirror the conditions of common occurrence in our country. Investments in manpower capacitance and the urgent and effective implementation of right procedures of manipulation, in a way to guarantee food according to the sanitary standards adequate to the health protection of the consumer public, are recommended.